Implementasi Kebijakan Pengelolaan Sampah Berbasis Zero Waste di Kota Banjarmasin - Devia Hetty Hernany; Amelia Puspita; Normajatun Normajatun (Journal on Education, 2023)
Implementation of waste management policies is a very important stage in the overall policy structure because through this procedure the overall policy process can be monitored for the level of success or lack of achievement of objectives. Policy implementation can be interpreted as the implementation of activities/activities referring to the guidelines that have been prepared so that the activities/activities that have been implemented can have an impact/consequences on society and can contribute to overcoming the problems that are the target of the program. Waste management must be carried out comprehensively so that it can provide economic benefits and environmental cleanliness. With the increasingly complicated waste problem, of course the government is required to overcome this waste problem. Currently, the government has created many programs to overcome waste problems in various corners. One of them is a waste management program. The concept of Zero Waste-Based waste management means treating waste to a zero or no leftover condition. By implementing the Zero Waste concept, the environment will truly be protected from the accumulation of waste, both organic and inorganic waste, so that more severe environmental damage can be avoided.